INOVASI MANAJEMEN PEMBELAJARAN INKLUSI UNTUK SEKOLAH BEBAS DISKRIMIASI - Famella, Shelvie; Hanafi, Imam; Anita, Anita (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the management of inclusive education in junior high schools without the presence of Special Assistance Teachers (GPK), as well as to identify strategies for enhancing the learning process for students with special needs (ABK) in inclusive classrooms. A qualitative descriptive approach was employed, utilizing interviews, classroom observations, and document analysis in three inclusive schools in Pekanbaru. Participants included school principals, classroom teachers, special education teachers, and parents of students with special needs. The findings reveal that inclusive education can still be effectively implemented without GPKs, provided that teachers receive sufficient training through programs such as In-House Training (IHT) and collaborate with external professionals. However, challenges remain, including rigid curricula, limited teacher preparedness, and inadequate teaching resources. The novelty of this research lies in its exploration of innovative inclusion management strategies based on internal teacher training and interdisciplinary collaboration, offering practical alternatives for resource-limited inclusive schools. These insights are expected to inform the development of more adaptive and sustainable inclusive education policies and practices.